Aplica????o da fotobiomodula????o no controle da dor em mulheres com disfun????o temporomandibular: ensaio cl??nico randomizado e duplo-cego - Herpich, Carolina Marciela (2018)
Temporomandibular dysfunction (TMD) is characterized by being a complex and multifactorial disorder, where functional and pathological alterations compromise temporomandibular joint, masticatory muscles, and other associated structures. Being pain is one of the most common and limiting clinical manifestations. One of the features used to treat it is photobiomodulation, however, the use of photobiomodulation that makes LLLT (low-level laser therapy) and LED (light emitting diode therapy) with varying wavelengths in the same device remains elucidated in the treatment of temporomandibular dysfunction, and in the application on the masseter muscles, both masseter and temporal and in the intraoral region. Based on the assumption that there is a need to investigate new therapeutic resources for the treatment of temporomandibular dysfunction, and to identify from a cross-sectional study the low threshold of pain and palpation mainly in the intraoral region, this study aimed to evaluate the effect of applied photobiomodulation in masticatory muscles in two protocols performed at different times; 1??) To evaluate the application of photobiomodulation in the masseter and temporal muscles bilaterally, in 2 weeks of treatment (6 sessions). 2??) Evaluate the application of intraoral photobiomodulation in the region of lateral pterygoid muscle bilaterally, both with evaluation immediately after 24h, 48h, and after 6 sessions. Evaluations were performed using the RDC / TMD questionnaire for diagnosis of dysfunction, visual analogue scale for pain analysis, digital pachymeter for evaluation of occlusal range of motion. For both studies, the results regarding pain intensity showed a significant difference (p???0.001) when compared to the pre and post treatment period. However, for range of motion, no statistical difference was observed between groups and moments of evaluation. Conclusion: The combination of superpulsed (905 nm), red (640 nm) and infrared (875 nm) light emitting diodes was effective in reducing pain intensity in women with temporomandibular disorders